INCREASING STUDENT’S ABILITY IN MASTERING VOCABULARY IN GRADE VII-1 SMP NEGERI 2 PERCUT SEI TUAN BY USING TWO STAY TWO STRAY STRATEGY - Basuki Anwar (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2023)
The research was conducted at SMPN 2 Percut Sei Tuan (PST). Thesubjects of this study were 32 students in class VII-1 SMPN 2 PST,consisting of 18 female students and 12 male students, in the 2022-2023 academic year. This study aims to determine whether the use ofthe Two Stay Two Stray technique can improve students' vocabulary mastery with reading text-based learning. This research includes 2cycles consisting of 7 meetings. The results of cycle 1 showed anincrease in the results of students' vocabulary mastery. The writer alsouses quantitative data in this study. If seen from the results obtainedfrom the pretest to the post test, the achievement of students'vocabulary mastery continues to increase significantly. Pretestlearning outcome data shows 11. 60% of students who are able to passa score of 75 (KKM). In cycle 1 there were 45.20% of students whoachieved a score of 75. Meanwhile in cycle 2 there were 91.20% ofstudents who passed a score of 75. Looking at the observationinstruments and diary notes also showed an increase in the quality ofthe teaching and learning process which was more conducive. So thewriter can conclude that the use of the Two Stay Two Stray approachin learning vocabulary in class VII-1 T.A 2022-2023 can significantlyimprove the results of students' vocabulary mastery and increasestudents' understanding of the text. Key Words : Increasing, Ability, Vocabulary, Strategy